Strategi Komunikasi Bisnis Melalui Media Sosial Di Era Digital Sekolah Musik YMS Antapani - yusra hamdani, zevy rizky (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
Every year there is an increase in internet users in Indonesia. The digital era forces business people to transform their activities from traditional systems to digitalization, including the use of social media. Nowadays, it is common to use social media for promotion and business development in order to reach the wider community. YMS Antapani Music School is a music school business located in the city of Bandung that has advantages over other music schools, including an industry-based music school, where students are not only introduced to music science but also the music industry in the form of recording activities. This study used descriptive qualitative method. YMS Antapani Music School has utilized social media for promotion, operations and business development, but it has not been optimal. Analysis results show that the number of followers on YMS Antapani social media has not reached a significant number, such as Instagram has 3,381 followers, Facebook has 419 followers, Youtube has 2,300 followers. Corrective steps are needed to introduce YMS Antapani to the wider community. For example, doing special handling in order to maximize the purpose of using social media itself, then turning it into a business account, and using influencers to promote in order to reach more people. Maximizing the use of social media can increase the number of YMS Antapani students.